Effectiveness of Common Cold Massage Education on Improving Mothers' Knowledge in Managing Coughs and Colds in Infants Aged 0–12 Months at TPMB Nita Bantur - Valiananastiti, Dita; Safitri, Rani (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2025)
Cough and cold in infants are common health issues caused by viral infections in the upper respiratory tract, which negatively affect the baby's quality of life. Massage therapy has been applied to relieve these symptoms, but many mothers still lack understanding about common cold massage and how to care for their babies when experiencing cough and cold. Most mothers tend to rely on applying telon oil or taking their babies to healthcare facilities for treatment. Massage has been practiced for centuries across the world. It can have a positive effect on the body and bring about beneficial physiological changes that can be measured scientifically. This study aims to determine the effect of an intervention on the participants' knowledge, as well as to examine the distribution of respondents based on education and age. The research used a quantitative method with a pre-experimental one-group pretest-posttest design. The paired t-test showed a significant difference between pre-test and post-test scores (p < 0.05). Most respondents had a senior high school education level (73.08%) and were aged 21–30 years (61.54%). These findings indicate that common cold massage is effective in improving mothers' understanding of how to manage cough and cold in infants, making it a valuable educational alternative in child care. Thus, the right approach can lead to meaningful change.